THE COVID-19 PANDEMIC PERSPECTIVE OF RELIGIOUS LITERATURE STUDIES IN BALI - Gede Sidi Artajaya (LP3M Universitas PGRI Mahadewa Indonesia, 2020)
The purpose of this study was to determine the covid-19 pandemic studied through religious literature in Bali both in sekala and niskala. The research design is descriptive qualitative which produces data in the form of written words related to Balinese local wisdom in terms of literature in response to the pandemic, presented by understanding the meaning of each sentence or paragraph passage in religious literature in Bali. Data collection was done by using literature or documentation methods. In niskala, various ceremonies and ceremonies are performed by the people to God, the ancestors, and bhuta kala. The offerings are in the form of banten pejati, banten peneduh gumi, tapak dara pandan, nyuh gading dan tridatu, serta segehan wong-wongan. All of that is based on the philosophy of Tri Hita Karana and Yadnya. The literary concept used is Widhi Sastra, Kanda Empat, and Dasa Aksara. The meaning of covid-19 from a literary perspective is to return the outbreak or Covid-19 to its respective functions and positions. Plague is a natural cycle that is certain to occur and is not to be expelled or destroyed. The results of this study are important to be understood by all people, especially in Bali, Indonesia, and the world to add insight related to the Balinese people's view of Covid-19 studied from religious literature and local wisdom.